2019
DOI: 10.1177/0018578719867664
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Lebanese Hospitalized Patients With Chronic Disease: A Cross-Sectional Study

Abstract: Background: In a hospitalized setting, malnutrition is known to increase patient’s mortality and lower the quality of life; therefore, it is essential to detect such cases and intervene at the earliest possible. The goal of this study is to estimate the rate of malnutrition in hospitalized Lebanese patients, explore its association with different factors, and create a simple tool to detect patients at high risk of malnutrition. Methods: One hundred and fifty Lebanese hospitalized patients, suffering at least f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Malnutrition is attributed to individual lifestyle behavior, socio-demographic characteristics, and economic, physiological, and pathological factors ( 35 ). In Lebanon, Mitri et al ( 36 ) reported that among older adults aged 65 years and above, women were significantly more at risk for malnutrition than men.…”
Section: The Global Burden Of Malnutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malnutrition is attributed to individual lifestyle behavior, socio-demographic characteristics, and economic, physiological, and pathological factors ( 35 ). In Lebanon, Mitri et al ( 36 ) reported that among older adults aged 65 years and above, women were significantly more at risk for malnutrition than men.…”
Section: The Global Burden Of Malnutritionmentioning
confidence: 99%
“…Surprisingly, oral health in adults, mainly older individuals, can affect their nutrition and may put them at risk of poor nutrition when dentures cannot cover their nutritional needs ( 36 ). Furthermore, depression and BMI are among the socio-demographic variables that are significantly associated with a greater risk of malnutrition among Lebanese older adults ( 35 ). For school-age children, malnutrition was mainly associated with age, time spent on electronic devices, skipping meals, and inadequate intake of nutrients ( 37 ).…”
Section: The Global Burden Of Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lebanon is a small country in the Middle East Region that is divided into five main districts with an estimated population of 6,847,712 and 144 hospitals comprising 11,742 beds ( 20 , 21 ). Studies on the prevalence of malnutrition in hospitalized patients have been modest with a small study reporting a rate of 37.4% in one hospital ( 22 ). The country has recently witnessed a severe financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, et al aimed to estimate the nutritional risk status of 150 Lebanese hospitalized patients from Centre Hospitalier Universitaire Notre Dame de Secours (CHU-NDS) hospital using the Mini Nutritional Assessment MNA tool. Results showed that 34.7% of the screened patients were at risk of malnutrition and 9.3% were malnourished (Choueiry et al, 2019).…”
Section: Prevalence Of Hospital Malnutritionmentioning
confidence: 99%